Asal-usul burung cenderawasih = The origins of cendrawasih (PT. Bhuana Ilmu Populer (BIP), 2019)
Di sebuah desa di Pegunungan Bumberi Hiduplah seorang perempuan sebatang kara Dia mencari buah untuk hidupnya sehari-hari Bahkan, sampai masuk ke hutan belantara In Bumberi Mountains there stood a small village Where a woman once lived who was deeply alone Fruits she sought often for work and for tillage To the depth of the jungle she searched on her own 02 Asal Usul Burung Cenderawasih